Maternal–Foetal Diabetes Modifies Neonatal Fc Receptor Expression on Human Leucocytes - de Souza, E. G.; Hara, C. C.P. [UNESP]; Fagundes, D. L.G.; de Queiroz, A. A.; Morceli, G. [UNESP]; Calderon, I. M.P. [UNESP]; Franï¿½a, E. L.; Honorio-Franï¿½a, A. C. (Wiley, 2016)
This study investigated the expression of the neonatal Fc receptor (FcRn) in maternal blood, cord blood and placental cells and determined IgG levels in maternal blood and cord blood from diabetic mothers. Peripheral blood, cord blood and placenta samples were collected from 26 mothers with normoglycaemia (non-diabetic, ND group) and 52 with hyperglycaemia (26 with mild gestational hyperglycaemia, MGH group, and 26 with type 2 diabetes mellitus, DM-2 group). Cells expressing CD19+ and FcRn were identified by flow cytometry. Total IgG and its subclasses were quantified by ELISA. Maternal blood from DM-2 and cord blood from MGH exhibited a higher proportion of CD19+ expression by B cells. DM-2 showed a lower proportion of CD19+ cells in placenta. FcRn expression increased in cells from cord blood and placenta from MGH. Maternal blood, cord blood and placenta cells from DM-2 showed lower FcRn expression. Blood IgG levels were lower in DM-2, and cord blood IgG levels were higher in MGH. The highest levels of IgG4 were detected in the blood of hyperglycaemic mothers. The highest IgG3 and IgG4 levels in cord blood were detected in MGH, and the lowest IgG2 and IgG3 levels in DM-2. Maternal hyperglycaemia compromised placental transfer of IgG1, IgG3 and IgG4. The results suggest that regardless of hyperglycaemia degree, it decreases FcRn expression in placenta and blood cells and compromises the production and transfer of antibodies from maternal blood to newborns.